Strengthening Community Readiness for a Possible Avian Influenza Resurgence - Nurrohman, Agus; Handayani, Oktia Woro Kasmini; Cahyati, Widya Hary; Rahayu, Sri Ratna (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Avian influenza (AI) continues to pose a significant zoonotic threat in communities where close contact between humans and poultry is common. In 2024–2025, several areas, including Semarang City, Klaten, Temanggung, and Purworejo, reported simultaneous poultry deaths that were subsequently confirmed as AI through laboratory testing. This study aimed to develop and evaluate a community-based educational model to enhance readiness for a potential AI resurgence in Semarang City. A research and development (R&D) approach was employed using the ADDIE framework, encompassing needs analysis, model development, expert validation, pilot testing, and refinement. A mixed methods approach assessed knowledge, attitudes, practices, self-efficacy, and health commitment, complemented by qualitative feedback from community cadres and local leaders. Independent t-tests compared pre- and post-intervention results between intervention and control groups. The intervention included a validated educational module, cadre capacity strengthening, and community-based surveillance components. The intervention group demonstrated statistically significant improvements across all assessed variables (p = 0.000), whereas the control group exhibited no significant changes (p > 0.05). The community-based educational model, known as KONMABUR (Komunitas Masyarakat Anti Flu Burung), proved effective in enhancing community preparedness for AI and shows potential for broader application in the prevention of other zoonotic diseases.